N-Chlorosulfonamide, a Useful Reagent for Chlorination of Various Carbanionic Substrates - Khazaei, Ardeshir; Habibzadeh, S. (Asian Journal of Chemistry, 2010)
N,N-Dichloro-4-methylbenzenesulfonamide prepared in high yield by treatment of corresponding sulfonamide with saturated solution of calcium hypochlorite, acts as site-selective electrophilic chlorinating agent towards carbanionic substrates. β-Ketoesters and β-diketones were chlorinated by this reagent without using any bases. The reagent can be recovered, rechlorinated and reused several times.